Penerapan Metode Dakwah Mauidzoh Hasanah Dalam Pembinaan Akhlak Santri Pondok Pesantren Sendang Drajat Jambon Ponorogo Tahun 2017 - Samitun, Samitun (Institut Agama Islam Sunan Giri Ponorogo, 2020)
Abstract Islam is da’wah. The meaning religion always encourage followers to always do da’wah actively, even back and forth Muslim are highly dependent and closely related to the activities of da’wah that he did. Cause the holy Qur’an says the activity da’wah with Ahsanu Qaula. With the other word can we conclude by da’wah is potition in the hall and happiness to the best Moslim religion. This article report from research, with some problem : How to doing da’wah at the Sendang Drajat Islamic Boarding School Jambon Ponorogo 2017?, What the method to make da’wah at the Sendang Drajat Islamic Boarding School Jambon Ponorogo 2017?, How to implement da’wah Mauhidzah Hasanah to guidance of santri morality at Sendang Drajat Islamic Boarding School 2017?. This research doing according kualitatif at education of religious, with procedure data collection by tecnic observer, interview, and documentation. Data in collection concerned with problematic teacher in process studying is dianalysis with descriptive kualitative to use concept is given from Miles and Huberman as data reduction, data presentation, anf conclution. Grounded of analysis data providable conclution : Implement da’wah at the Sendang Drajat Islamic Boarding School Jambon Ponorogo covers some institution social, Islamic boarding school has played an important role in several countries. In carrying out moral character of santri Sendang Drajat Islamic Boarding School, the boarder of the lodge use method al-mauhidzah hasanah because having searched the Mau’idzah Hasanah is contains a word into heart with loving full and into feeling with full of tenderness, don’t dismantle or expose the faults of others because of the gentle weakness in advising always can to melt a hard heart and tame a wild heart. Method is often to use mauhidzah hasanah with purpose to give advice with tenderness. This hope santri can accept advices from father in the boarding. The step for to implementation method da’wah mauhidzah hasanah to guidance character santri at Islamic Boarding School calling santri problem and giving a punishment to not repeat the false again. And then to give punishment to get the best. Key word Method Da’wah, Morality Guidance